2021
DOI: 10.21107/personifikasi.v12i1.8382
|View full text |Cite
|
Sign up to set email alerts
|

Wisata Super Premium Labuan Bajo: Mengkaji Peran Langsung dan Tidak Langsung Terhadap Visiting Intention Ditinjau dari Destination Image dan Tourist Expectation

Abstract: The Indonesian government was planning a super premium tour of Labuan Bajo to be realized in 2020, but the change in this type of tourism resulted in various changes in travel behaviour. This study aims to examine the direct and indirect role of visiting intentions to Labuan Bajo through the destination image and tourist expectation. This research involved 141 tourists who have been and who have a desire to visit Labuan Bajo. Researchers used three scales of analysis, namely the scale of destination image, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Another study showed the potential for a tsunami originating from Sletan Nusa Tenggara (Pradjoko & Muhari, 2020). Meanwhile, studies directly related to Labuan Bajo are mostly linked to tourism development in terms of potential, policy, socio-economic, urban development, and tourist potential (Akhrani & Azhar, 2021;Andriani Moi, 2017;Idris, Selva, & Destari, 2019;Sugiarto & Gusti, 2020). Therefore, it is essential to study the potential for a tsunami in the north of Labuan Bajo.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed the potential for a tsunami originating from Sletan Nusa Tenggara (Pradjoko & Muhari, 2020). Meanwhile, studies directly related to Labuan Bajo are mostly linked to tourism development in terms of potential, policy, socio-economic, urban development, and tourist potential (Akhrani & Azhar, 2021;Andriani Moi, 2017;Idris, Selva, & Destari, 2019;Sugiarto & Gusti, 2020). Therefore, it is essential to study the potential for a tsunami in the north of Labuan Bajo.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of cultural tourism destinations that are commonly visited are historical sites, art and architecture, festivals and events, religious sites, culinary experiences, and music and dance. Overall, cultural tourism destinations offer tourists the opportunity to experience the unique heritage and culture of a particular region or country, and can provide a deeper understanding and appreciation of the destination (Asa Akhrani et al, 2021;Cui et al, 2018 ).…”
Section: Destinations Types Of Tours Travel Optionsmentioning
confidence: 99%
“…Daya tarik yang luar biasa ini, pemerintah mendeklarasikan Kabupaten Manggarai Barat sebagai kota super premium tahun 2020. Perubahan status daerah wisata ini memiliki berbagai dampak seperti perilaku wisatawan, pelaku wisata, warga lokal maupun pemangku kebijakan (Akhrani et al, 2021).…”
Section: Pendahuluanunclassified